An extensive review of energy storage system for the residential renewable energy system - Mustaza, M. S. A.; M. Ariff, M. A.; Ramli, Sofia Najwa (2019)
Energy storage system (ESS) plays a prominent role in renewable energy (RE) to overcome the intermittent of RE energy condition and improve energy utilization in the power system. However, ESS for residential applications requires specific and different configuration. Hence, this review paper aims to provide information for system builders to decide the best setup configuration of ESS for residential application. In this paper, the aim is to provide an insight into the critical elements of the energy storage technology for residential application. The update on ESS technology, battery chemistry, battery charging, and monitoring system and power inverter technology are reviewed. Then, the operation, the pro, and cons of each variant of these technologies are comprehensively studied. This paper suggested that the ESS for residential ESS requires NMC battery chemistry because it delivers an all-rounded performance as compared to other battery chemistries. The four-stages constant current (FCC) charging technique is recommended because of the fast charging capability and safer than other charging techniques reviewed. Next, the battery management system (BMS) is recommended to adapt in advance machine learning method to estimate the state of charge (SOC), state of health (SOH) and internal temperature (IT) to increase the safety and prolong the lifespan of the batteries. Finally, these recommendations and solutions aimed to improve the utilization of RE energy in power system, especially in residential ESS application and offer the best option that is available on the shelf for the residential ESS application in the future.